Agricultural change and rural poverty: a synthesis - Mellor, John W.; Desai, Gunvant M. (International Food Policy Research Institute, 1985)
It is the large variations in rural poverty over time and across space that provide the laboratory for understanding the causes of rural poverty and hence the means of its alleviation. The temporal variations in poverty include not only the secular decline incident to decades-long processes of growth and the violent short-term changes brought about by famine but also the substantial intermediate-term undulations that can cause the number of people in absolute poverty to vary by 50 percent or more, The spatial variations in poverty eccompass situations that differ widely in terms of the average income of the population, the land-tenure systems, and the institutional organization as well as those that are uite similar.